2012
DOI: 10.1039/c2sm06859a
|View full text |Cite
|
Sign up to set email alerts
|

Surface wave on a particle raft

Abstract: International audienceThe mechanical properties of particle laden interfaces are investigated by studying capillary wave propagation along the interface. Interfaces are coated with monodisperse silica hydrophobic particles with diameters ranging from 35 mm to 159 mm. The surfaces are prepared with a particle density just above that required for random close packing, so that no macroscopic wrinkles can be observed. Measurements of wave celerity versus wavelength and a comparison of the results with theory allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 26 publications
0
57
1
Order By: Relevance
“…From ΔP − we estimate the expected value for this modulus: E ≈ 20 kPa. This value is at least 100 times larger than the values reported for particles rafts [23,24] and classical armored drops [16]. This highlights again how the strength of gas marbles differs from the strength of classical armored bubbles and drops.…”
Section: Fig 4 Normalized Critical Overpressures (δPcontrasting
confidence: 44%
“…From ΔP − we estimate the expected value for this modulus: E ≈ 20 kPa. This value is at least 100 times larger than the values reported for particles rafts [23,24] and classical armored drops [16]. This highlights again how the strength of gas marbles differs from the strength of classical armored bubbles and drops.…”
Section: Fig 4 Normalized Critical Overpressures (δPcontrasting
confidence: 44%
“…This result indicates that the elasticity at the interface between the air and the foam can be neglected at first order thus leading to no supplementary contribution in the dispersion relation (1). 49 For a continuous harmonic forcing at the resonant frequency f 1 and lateral displacement amplitude X 0 = 1 mm, the maximum amplitude of sloshing decreases significantly for increasing foam thicknesses as shown in figure 4 (Multimedia View). Indeed, without foam, the free-surface has a maximum amplitude of the order of 1 cm; the addition of only ξ = 5 layers of bubbles leads to a maximum amplitude of the order 1 mm, which is a factor of ten reduction.…”
Section: A Experimental Observations In a Hele-shaw Cellmentioning
confidence: 98%
“…In that model, the particles were assumed to be perfectly rigid when compared to the interface as a whole, the Poisson ratio was derived geometrically by describing the deformation of a rhombic cell, and the bending stiffness was assumed to be equivalent to that of a solid thin film of thickness equal to the diameter of the particles. Planchette et al [22] recently showed through independent measurements of the bending stiffness of particle laden surfaces that the assumption of Vella et al [10] capture the right scaling of the bending stiffness with particle size, but over predict its magnitude by a factor of about two. Following Vella et al's work [10], an estimate for the buckling wavelength is obtained:…”
Section: Introductionmentioning
confidence: 98%